2009
DOI: 10.1590/s1984-82502009000100005
|View full text |Cite
|
Sign up to set email alerts
|

Assistência ao diabetes no Sistema Único de Saúde: análise do modelo atual

Abstract: O sistema de saúde nacional, impulsionado por contextos econômicos restritivos, passou por uma reestruturação organizacional na década de 1990, voltada à atenção primária. Apesar das reformas, a incidência de diabetes mellitus ainda atinge elevadas proporções. Devido à alta morbi-mortalidade, a prevenção dessa morbidade tem-se tornado foco atual, fazendo-se necessário o desenvolvimento de programas eficazes e viáveis ao Sistema Único de Saúde, tais como ênfase na prevenção primária, controle da incidência e co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
31

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 31 publications
(32 reference statements)
0
13
0
31
Order By: Relevance
“…In relation to public services, governments and leaders discuss the issue of drug supply and financing strategies, but few recognize that medicines are only a tool for delivering a service and generally do not care about structuring and Organization of this. The majority of pharmacies at the Basic Health Units (UBS) do not count on the presence of the pharmacist who could provide better assistance to the health user, presents reduced physical space and works mostly as a storage place for medicines and many Of the times, it has served only as a medicine delivery place, and there is no pharmaceutical-user interaction [21].…”
Section: Resultsmentioning
confidence: 99%
“…In relation to public services, governments and leaders discuss the issue of drug supply and financing strategies, but few recognize that medicines are only a tool for delivering a service and generally do not care about structuring and Organization of this. The majority of pharmacies at the Basic Health Units (UBS) do not count on the presence of the pharmacist who could provide better assistance to the health user, presents reduced physical space and works mostly as a storage place for medicines and many Of the times, it has served only as a medicine delivery place, and there is no pharmaceutical-user interaction [21].…”
Section: Resultsmentioning
confidence: 99%
“…According to Guidoni et al 31 , the Family Health Strategy, currently the main primary care mechanism in the SUS, fails to fully meet with the prevention and health promotion recommendations for type 2 diabetes mellitus, thus generating gaps that are ultimately reflected in heavy expenditures on high-complexity expenditures for diabetics. Evaluating the profile of type 2 diabetes mellitus patients hospitalized in the SUS, Artilheiro et al 32 showed that the majority reported treatment for systemic arterial hypertension or some comorbidity associated with type 2 diabetes mellitus, such as DN, DR, or peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, health services need to cope with rising costs in contrast to scarce resources [37]. This scenario becomes a challenge for the health system, considering the increase in the life expectancy of DM patients.…”
Section: Costs Associated With the Treatment Of Diabetes Mellitusmentioning
confidence: 99%